Steamships JEFFERSON and PRINCESS MAY at dock, Skagway, ca. 1904 - Nowell, Frank H., 1864-1950 (1904)
Caption on image: Photo by F.H. Nowell, 6333 On verso of image: S.S. Jefferson, Skagway, Alaska The JEFFERSON was a wooden passenger steamer built in 1903 at Tacoma. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number